2023
DOI: 10.1186/s12905-022-02142-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of early-onset breast cancer: a comparative analysis of cases from across Ghana

Abstract: Background Breast cancer is the commonest cancer diagnosed globally and the second leading cause of cancer-related mortality among women younger than 40 years. This study comparatively reviewed the demographic, pathologic and molecular features of Early-Onset Breast Cancer (EOBC) reported in Ghana in relation to Late Onset Breast Cancer (LOBC). Methods A descriptive, cross-sectional design was used, with purposive sampling of retrospective histopat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
3
2
1
Order By: Relevance
“…The mean age in this study was comparable with previous studies conducted in Ethiopia by Gemta et al (44 years), Kantelhardt et al (43 years), and Ersumo (44.77 years) [ 13 , 17 , 18 ]. Similar findings were also reported from other African counties with a mean age ranging from 45.8 to 48.7 years [ 19 , 20 , 21 , 22 , 23 ]. In contrast to these studies, the mean age of BC patients at diagnosis is higher in high-income countries [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean age in this study was comparable with previous studies conducted in Ethiopia by Gemta et al (44 years), Kantelhardt et al (43 years), and Ersumo (44.77 years) [ 13 , 17 , 18 ]. Similar findings were also reported from other African counties with a mean age ranging from 45.8 to 48.7 years [ 19 , 20 , 21 , 22 , 23 ]. In contrast to these studies, the mean age of BC patients at diagnosis is higher in high-income countries [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…[13,17,18]. Similar findings were also reported from other African counties with a mean age ranging from 45.8 to 48.7 years [19][20][21][22][23]. In contrast to these studies, the mean age of BC patients at diagnosis is higher in high-income countries [24].…”
Section: Clinicopathological Featuressupporting
confidence: 66%
“…Additionally, the frequency of TNBC and Luminal A were higher among patients with early-onset BC compared with late-onset BC. This agrees with the findings of Akakpo et al [24] in Ghana. In this study, the highest frequency of obesity was found among patients with Luminal A breast cancer (85.7%).…”
Section: Discussionsupporting
confidence: 94%
“…The frequency of TNBC recorded in this study (34.2%) is higher than the frequency of 24.7% and 27% reported by Akakpo et al . [24] and Huo et al . [25] in Ghana and African women, respectively but lower than the frequency (82%) reported by Stark et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation